A qualitative exploration of driving stress and driving discourtesy. (September 2018) - Scott-Parker, B.; Jones, C.M.; Rune, K.; Tucker, J.
Highlights: Focus groups (n = 38 drivers) revealed discourteous and stressful driving experiences. Theme 1: driving context including infrastructure, where, when and what driving. Theme 2: other road user behaviours like merging, tailgating, illicit drugs. Theme 3: self as road user including behavioural and emotional reactions like anger. Abstract: Background: Driving courtesy, and conversely driving discourtesy, recently has been of great interest in the public domain. In addition, there has been increasing recognition of the negative impact of stress upon the individual's health and wellbeing, with a plethora of interventions aimed at minimising stress more generally. The research literature regarding driving dis/courtesy, in comparison, is scant, with a handful of studies examining the dis/courteous driving behaviour of road users, and the relationship between driving discourtesy and driving stress. Aim: To examine courteous and discourteous driving experiences, and to explore the impact of stress associated with such driving experiences. Method: Thirty-eight drivers (20 females) from the Sunshine Coast region volunteered to participate in one of four 1–1.5 h focus groups. Content analysis used the verbatim utterances captured via an Mp3 device. Results: Three themes pertaining to stressful and discourteous interactions were identified. Theme one pertained to the driving context: road infrastructure (eg, roundabouts, roadwork), vehicles (eg, features), location (eg, country vs city, unfamiliar areas), and temporal aspects (eg, holidays). Theme two pertained to other road users: their behaviour (eg, tailgating, merging), and unknown factors (eg, illicit and licit drug use). Theme three pertained to the self as road user: their own behaviours (eg, deliberate intimidation), and their emotions (eg, angry reaction to other drivers, being in control). Discussion and conclusions: Driving dis/courtesy and driving stress is a complex phenomenon, suggesting complex intervention efforts are required. Driving discourtesy was reported as being highly stressful, therefore intervention efforts which encourage driving courtesy and which foster emotional capacity to cope with stressful circumstances appear warranted.